Three-dimensional visual modelling of geological information of hydraulic engineering based on surface constraint reconstruction. (28th March 2019) - Jing, Wei; Xuejuan, Wang; Xiaolong, Wen
In order to solve the problems of big errors in results and weak spatial expression ability of the existing three-dimensional visual modelling methods for geological information of hydraulic engineering, a three-dimensional visual modelling method of geological information of hydraulic engineering based on surface constraint reconstruction is proposed. Geological information of large-scale hydraulic engineering is loaded into an expert image processing system through the sparse scatterplot analysis method to construct a spatial scatterplot model for geological information distribution; adaptive feature matching is performed to the geological information through the template matching method, and edge contour features of the three-dimensional visual image are extracted through surface interpolation and vector edge clipping method; information enhancement and local profile horizon reconstruction are performed for the three-dimensional reconstruction image about geological information of large-scale hydraulic engineering through the wavelet domain feature decomposition method. Simulation results show that the method proposed in this paper can provide high accuracy in visual modelling of large-scale hydraulic engineering geological information with error of only 0.04 mm, strong spatial expression ability of three-dimensional visual modelling and relatively high matching of feature points, so it can provide good three-dimensional reconstruction effect of geological information.